Eastern Scotian Shelf trophic dynamics: A review of the evidence for diverse hypotheses. (November 2015) - Sinclair, Michael; Power, Michael; Head, Erica; Li, William K.W.; McMahon, Michael; Mohn, Robert; O'Boyle, Robert; Swain, Douglas; Tremblay, John
Highlights: The evidence for respectively top-down control and bottom-up control of the ecosystem features of the Eastern Scotian Shelf off Atlantic Canada from the 1970s to the present is evaluated. There is limited evidence in support of the fisheries induced trophic cascade hypothesis. Stratification/nutrient/plankton trends are generally consistent with climate variability hypothesis. It is concluded that a combination of concurrent top-down forcing by grey seals and bottom forcing due to climate variability is consistent with the aggregate observations on the ecosystem decadal trends. Abstract: Two hypotheses have been proposed to account for trophic dynamic control of the eastern Scotian Shelf ecosystem off Atlantic Canada: (1) top-down: fishery induced trophic cascade and (2) bottom-up: climate variability . We evaluate the evidence in support of these hypotheses: including observations on top-down drivers (fishing effort and predation by grey seals), bottom-up drivers (nutrient supply and water column stratification), and the several trophic levels (groundfish, macro-invertebrates, small pelagic fish, and plankton). There is limited support for the fishery-induced trophic cascade hypothesis. The predictions of the climate variability hypothesis are generally met for the lower and middle trophic levels, but the ongoing high levels of natural mortality of groundfish are not accounted for. We propose an alternative hypothesis encompassing concurrent top-down and bottom-up processes, and conclude that many species of groundfish (including cod) and small pelagic fish stocks (including herring) will not recover with the ongoing high levels of natural mortality generated by grey seal predation. Predictions on future trends in abundance of the commercially important macro-invertebrate species (lobster, snow crab, and shrimp) are not possible based on the available evidence.